The Development of an ex vivo Flow System to Assess Acute Arterial Drug Retention of Cardiovascular Intravascular Devices - Cooper, Kathryn; Cawthon, Claire V.; Goel, Emily; Atigh, Marzieh; Christians, Uwe; Yazdani, Saami K. (Frontiers in Medical Technology, 2021)
Purpose: The goal of this study was to develop an ex vivo system capable of rapidly evaluating arterial drug levels in living, isolated porcine carotid arteries. Methods: A vascular bioreactor system was developed that housed a native porcine carotid artery under physiological flow conditions. The ex vivo bioreactor system was designed to quantify the acute drug transfer of catheter-based drug delivery devices into explanted carotid arteries. To evaluate our ex vivo system, a paclitaxel-coated balloon and a perfusion catheter device delivering liquid paclitaxel were utilized. At 1-hour post-drug delivery, arteries were removed, and paclitaxel drug levels measured using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Parallel experiments were performed in a pig model to validate ex vivo measurements. Results: LC-MS/MS analysis demonstrated arterial paclitaxel levels of the drug-coated balloon-treated arteries to be 48.49±24.09 ng/mg and the perfusion catheter-treated arteries to be 25.42±9.74 ng/mg at 1 hour in the ex vivo system. Similar results were measured in vivo, as arterial paclitaxel concentrations were measured at 59.23±41.27 23.43±20.23 ng/mg for the drug-coated balloon-treated arteries and 23.43±20.23 ng/mg for the perfusion catheter-treated arteries. Overall, no significant differences were observed between paclitaxel measurements of arteries treated ex vivo versus in vivo. Conclusion: In conclusion, this system represents the first validated ex vivo pulsatile system to determine pharmacokinetics in a native blood vessel. This work provides proof-of-concept of a quick, inexpensive, pre-clinical tool to study acute drug tissue concentration kinetics of drug-releasing interventional devices.